Book Review of Fight Club Written By Chuck Palahniuk - Nugroho, Adityo Widhi (LANTERN (Journal on English Language, Culture and Literature), 2016)
The main purpose of this writing is to review Fight Club by Chuck Palahniuk. The writer will discuss the strengths and weaknesses of this novel . The writer decided to choose Fight Club as final project because it is his favorite novel. Fight Club is a very interesting novel although it is hard to understand and disturbing because by showing the consumerism behaviour in this novel, Chuck Palahniuk tries to convey the message that the consumerism behaviour of society nowadays has become worse than ever.